The Effect of the Time Structure of Laser Pulse on Temperature Distribution and Thermal Stresses in Homogeneous Body with Coating - Yevtushenko, Aleksander; Rozniakowska-Klosinska, Malgorzata (IntechOpen, 2010)
None